(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to determine the average height and analyzed associated factors among students at N’Trang Long Ethnic Minority Boarding High School in Dak Lak province in 2025. Subject and method: A cross - sectional study was conducted on 467 students at N’Trang Long Ethnic Minority Boarding High School in Dak Lak province in March 2025. Data were collected through structured group interviews and direct physical measurements, including anthropometric indicators and body composition parameters. Multivariable linear regression analysis was applied to identify factors associated with students’ height. Results: The mean height was 166.1 ± 6.4 cm for male students and 155.4 ± 5.2 cm for females. Multivariable regression analysis revealed significant associations between height and muscle mass (p < 0.001), sex (p < 0.001), body fat percentage (p < 0.001), and number of siblings (p = 0.001). Physical activity level was not statistically significant in the multivariable model. Conclusion: The average height of the students was lower than that of 18-year-old Vietnamese youth in 2020. The findings highlight the need for targeted physical development interventions, particularly for ethnic minority adolescents, to improve their growth outcomes.